Factors Influencing the Well-Being of Special Education Teachers - Utomo, Imam Yuwono (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The progress of special education teachers' students is influenced by their well-being, which is crucial to their mental health. It is vital to comprehend teacher well-being and its effects on the teaching and learning nexus in this setting where these difficulties are interrelated. This study sought to learn more about the psychological factors influencing special education teachers' well-being in Banjarmasin. We evaluated how work engagement and emotional intelligence (EI) relate to teachers' well-being. The latest study included 496 special education instructors in total. The findings revealed that Emotional Intelligence and work engagement were positively correlated with special education teachers' well-being and (2) work engagement acted as a negotiator between EI and well-being. It is suggested that politicians and educational institutions take these measures to support the well-being of special education instructors.